The Unemployment of Highly Educated People in Romania. A Panel VAR Approach - Simionescu, Mihaela; Naroș, Maria Simona (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2019)
The insertion of graduates of higher education on the labor market is one of the problems faced by the Romanian labor market. Based on a VAR model in the panel, the number of unemployed with higher education in Romania is explained in correlation with variables related to the educational environment. As the number of graduates, the number of teaching staff and the number of faculties increase the unemployment rate among people with higher education also increases slightly, showing that they have not immediately integrated into the labor market. A shock (an innovation) in the series of unemployed numbers results in an increase in the number of unemployed and a long-term stabilization of the influence to positive values. A shock to the data series on the number of graduates, the number of faculties and teaching staff does not have an immediate effect on the number of unemployed with higher education.